CHALLENGES AND SOLUTIONS IN THE APPLICATION OF CERAMICS ON ZIRCONIA FRAMEWORK - Hryn, Vasyl (European Journal of Interdisciplinary Issues, 2025)
This work is devoted to the study of the main challenges that arise when applying facing ceramics to zirconia frameworks, as well as the identification of effective solutions to overcome them and increase the clinical success and durability of ceramic restorations. In modern dental practice, zirconia frameworks are used for the manufacture of fixed orthopedic structures. This choice is due to their exceptional biocompatibility, strength, and aesthetic properties. However, the combination of ceramic veneers with zirconia still poses significant challenges that can lead to chipping, cracking, and premature failure of the restoration. This article analyzes the key problems encountered when applying ceramics to zirconia frameworks, including differences in thermal expansion coefficients, insufficient adhesion, pore formation, and the impact of process disruptions. The paper discusses modern solutions and strategies to overcome these difficulties, such as improving zirconia surface preparation protocols, using intermediate binder layers, optimizing ceramic firing regimes, and selecting ceramic materials with adapted properties. It has been shown that it is of great importance to follow optimal firing protocols that include a controlled level of heating and gradual cooling. Such conditions prevent thermal shock and stress generation. In addition, the rational design of restorations, which provides for rounding of the corners of the framework, minimal and uniform thickness of the facing ceramic, as well as maximum support of the ceramic by the zirconia framework in functionally loaded areas, is crucial for increasing the mechanical stability and durability of the structure. The results obtained may be useful for dental technicians, orthopedists, and scientists in the field of dental care.